1998
DOI: 10.1590/s0074-02761998000700046
|View full text |Cite
|
Sign up to set email alerts
|

Chronic carriers of hepatitis B surface antigen in an endemic area for schistosomiasis mansoni in Brazil

Abstract: Data on the association of schistosomiasis and hepatitis B in field-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The prevalence in Northern, Central and Southern governorates was more or less similar. It is common to find a heterogeneous pattern of HBV endemicity inside the same country [19], [20]. Similar to the pattern known worldwide [4], [8], males were at higher risk of contracting HBV infection compared to females.…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence in Northern, Central and Southern governorates was more or less similar. It is common to find a heterogeneous pattern of HBV endemicity inside the same country [19], [20]. Similar to the pattern known worldwide [4], [8], males were at higher risk of contracting HBV infection compared to females.…”
Section: Discussionmentioning
confidence: 68%
“…Hyams et al (1987) concluded that there was no correlation between S. mansoni infection, with or without hepatosplenomegaly and HBsAg positivity. The study of Serufo et al (1997) in endemic area from Minas Gerais also did not show association between schistosomiasis and HBV. In Brazil, Guimarães (1975) recorded 4.4% of patients infected with hepatitis B virus among patients with hepatosplenic schistosomiasis (as compared to 1.5% in the hepatointestinal form and 0.6% in controls); Lyra (1976) found 7.8% of HBV markers in the hepatosplenic form of schistosomiasis (as compared to 1.5% in the hepatointestinal form and 1.3% in controls).…”
Section: Discussionmentioning
confidence: 72%
“…The results were not uniform, some of them showing association between B virus and schistosomiasis 2,19,20,37,52,61 , while others did not demonstrated a higher prevalence 27,28,40,73 or a higher rate of chronification of hepatitis 69 .…”
Section: Introductionmentioning
confidence: 87%